Understanding Ongoing Challenges in the Small Business Sector’s Access to External Finance Since Storey (1994): A Thirty-Year Retrospective - Paul Jones (Palgrave Studies in Entrepreneurship and Society, 2025)
The ongoing challenges to accessing external finance by the “small business sector” is longstanding. Yet, in the case of the United Kingdom (UK), it was formally documented in the inter-war period in 1930 (Storey in Understanding the Small Business Sector, Routledge, 1994a). Research prior to 1931 found that small business creation, sustainability, and economic growth are critical; and that the small business sector offers macroeconomic stability and economic growth (Macmillan Report in Report of the Committee on Finance and Industry. Cmd. 3897, 1931).